The CO donor CORM‐2 inhibits LPS‐induced vascular cell adhesion molecule‐1 expression and leukocyte adhesion in human rheumatoid synovial fibroblasts. (June 2014) - Chi, Pei‐Ling; Chuang, Yu‐Chen; Chen, Yu‐Wen; Lin, Chih‐Chung; Hsiao, Li‐Der; Yang, Chuen‐Mao
<x xml:space="preserve">Abstract</x> Background and Purpose Infection with Gram‐negative bacteria has been recognized as an initiator of rheumatoid arthritis, which is characterized by chronic inflammation and infiltration of immune cells. Carbon monoxide (CO) exhibits anti‐inflammatory properties. Here we have investigated the detailed mechanisms of vascular cell adhesion molecule‐1 (VCAM‐1) expression induced by LPS and if CO inhibited LPS‐induced leukocyte adhesion to synovial fibroblasts by suppressing VCAM‐1 expression. Experimental Approach Human rheumatoid arthritis synovial fibroblasts (RASFs) were incubated with LPS and/or the CO‐releasing compound CORM‐2. Effects of LPS on VCAM‐1 levels were determined by analysing mRNA expression, promoter activity, protein expression, and immunohistochemical staining. The molecular mechanisms were investigated by determining the expression, activation, and binding activity of transcriptional factors using target signal antagonists. Key Results CORM‐2 significantly inhibited inflammatory responses in LPS‐treated RASFs by down‐regulating the expression of adhesion molecule VCAM‐1 and leukocyte infiltration. The down‐regulation of LPS‐induced VCAM‐1 expression involved inhibition of the expression of phosphorylated‐NF‐κB p65 and AP‐1 (p‐c‐Jun, c‐Jun and c‐Fos mRNA levels). These results were confirmed by chromatin immunoprecipitation assay to detect NF‐κB and AP‐1 DNA binding activity. Conclusions and Implications LPS‐mediated formation of the TLR4/MyD88/TRAF6/c‐Src complex regulated NF‐κB and MAPKs/AP‐1 activation leading to VCAM‐1 expression and leukocyte adhesion. CORM‐2, which liberates CO to elicit direct biological activities, attenuated LPS‐induced VCAM‐1 expression by interfering with NF‐κB and AP‐1 activation, and significantly reduced LPS‐induced immune cell infiltration of the synovium.